2015
DOI: 10.1021/acs.jpcb.5b00921
|View full text |Cite
|
Sign up to set email alerts
|

Novel Guanidinium-Based Ionic Liquids for Highly Efficient SO2 Capture

Abstract: The application of ionic liquids (ILs) for acidic gas absorption has long been an interesting and challenging issue. In this work, the ethyl sulfate ([C2OSO3](-)) anion has been introduced into the structure of guanidinium-based ILs to form two novel low-cost ethyl sulfate ILs, namely 2-ethyl-1,1,3,3-tetramethylguanidinium ethyl sulfate ([C2(2)(C1)2(C1)2(3)gu][C2OSO3]) and 2,2-diethyl-1,1,3,3-tetramethylguanidinium ethyl sulfate ([(C2)2(2)(C1)2(C1)2(3)gu][C2OSO3]). The ethyl sulfate ILs, together with 2-ethyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 52 publications
(105 reference statements)
0
18
1
Order By: Relevance
“…At a temperature of 40 ∘ C, the molar ratio of SO 2 to IL was about 0.4 at the SO 2 concentration of 2000 ppm for [TMG][PBE] . When SO 2 concentration was 2% by volume in mixed gas of N 2 and SO 2 , the equilibrium absorption of [TMG][PBE] was 0.72 mol SO 2 mol −1 of IL, which was higher than the value of 0.51 for [TMG]L at the same temperature reported by Ren et al 23 When the mixed gas of N 2 and SO 2 with SO 2 content of 8% by volume was absorbed by [TMG][PBE] at 1 bar pressure and 40 ∘ C, the equilibrium molar ratio of SO 2 to [TMG][PBE] was 1.45:1, which was more than the equilibrium absorption of [TMG]L under the same condition, 5 and far more than the saturated absorption of the [NTf 2 ]-based ILs at SO 2 pressure of 0.1 bar and 20 ∘ C. 7…”
Section: The Behavior Of So 2 Absorptionmentioning
confidence: 91%
See 1 more Smart Citation
“…At a temperature of 40 ∘ C, the molar ratio of SO 2 to IL was about 0.4 at the SO 2 concentration of 2000 ppm for [TMG][PBE] . When SO 2 concentration was 2% by volume in mixed gas of N 2 and SO 2 , the equilibrium absorption of [TMG][PBE] was 0.72 mol SO 2 mol −1 of IL, which was higher than the value of 0.51 for [TMG]L at the same temperature reported by Ren et al 23 When the mixed gas of N 2 and SO 2 with SO 2 content of 8% by volume was absorbed by [TMG][PBE] at 1 bar pressure and 40 ∘ C, the equilibrium molar ratio of SO 2 to [TMG][PBE] was 1.45:1, which was more than the equilibrium absorption of [TMG]L under the same condition, 5 and far more than the saturated absorption of the [NTf 2 ]-based ILs at SO 2 pressure of 0.1 bar and 20 ∘ C. 7…”
Section: The Behavior Of So 2 Absorptionmentioning
confidence: 91%
“…Shang et al 6 also synthesized three guanidinium-based ionic liquids which had showed high SO 2 absorption rate. These ILs could absorb SO 2 by both physical and chemical interactions while physical absorption plays an important role at the temperature of 40 ∘ C. Lu et al 7 introduced the ethyl sulfate ([C 2 OSO 3 ] − ) anion into the structure of guanidinium-based ILs to form two novel low-cost ethyl sulfate ILs. These guanidinium ethyl sulfate ILs showed good performance for SO 2 capture.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ionic liquids (ILs) have been demonstrated to be promising media for the recovery of CO 2 , hydrogen sulfide (H 2 S), sulfur dioxide (SO 2 ) and NH 3 owing to their negligible volatility, excellent thermal stability, remarkable solubility and structure designability. Compared to the water scrubbing method, the goals of no waste water discharge, lower energy consumption and high purity NH 3 recovery can be achieved by using ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [15] first reported an IL-1,1,3,3-tetramethylguanidinium lactate ([TMG]L) for SO 2 absorption from a gas mixture of SO 2 and N 2 , and the result showed that 1 mol [TMG]L could selectively capture 0.978 mol SO 2 at 40 °C. Later, many other ILs, including hydroxyl ammonium ILs [16,17], ether-functionalized ILs [18][19][20], imidazolium-based ILs [21][22][23], guanidinium-based ILs [24][25][26], pyridinium-based ILs [27,28], anion-functionalized ILs [29,30], and, more recently, deep eutectic solvents [31][32][33], were investigated for SO 2 absorption.…”
Section: Introductionmentioning
confidence: 99%